Reconstructing the neuromuscular ground pattern of phylactolaemate bryozoans: new data from the Lophopodidae - J. Bibermair; T. S. Wood; R. Chaichana; T. Schwaha (BMC Ecology and Evolution, 2022)
Abstract Background The solely freshwater inhabiting Phylactolaemata is a sister taxon to all other bryozoans. Among phylactolaemates, Lophopodidae represents an early branching clade that is therefore crucial for ground pattern reconstruction. While more recent morphological data of most phylactolaemate families are present, data of lophopodids are scarce. The genus Asajirella especially, which was previously assigned to the family Pectinatellidae, lacks any detailed analysis with more recent morphological methods. Results This study provides the first morphological analyses of three lophopodid species using serial-sectioning histology and 3D reconstruction, but also immunocytochemical stainings and confocal laserscanning microscopy. There are several lophopodid-specific traits in the nervous system such as the large ganglion with extensive lumen and two prominent protrusions referred to as epistomial horns. The epistome in all lophopodids is rather small and dome-shaped. Contrary to previous reports, we can confirm that duplicature bands insert at the tentacle sheath rather than the diaphragmatic sphincter in all phylactolaemates. The morphology of the digestive tract of lophopodids is identical to other phylactolaemates and possesses exclusively circular muscles. Conclusions Altogether, this study fills significant gaps in our knowledge on phylactolaemate neuromuscular systems and general morphology. It shows that the insertion of the duplicature bands at the tentacle sheath and the circular musculature of the digestive tract to be the ground pattern in phylactolaemates. In addition, we found apomorphic characters for lophopodids such as the dome-shaped epistome with its musculature and the voluminous ganglion with its epistomial horns, which aid in defining and delineating the family.